EFFICACY OF TRITICUM AESTIVUM (WHEATGRASS) AGAINST ARSENIC INDUCED HEPATIC DAMAGES - NAREDA, ANITA; KUMAR, MADHU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Arsenic is a metalloid element that is one of the most important global environmental toxicants and is found in both organic and inorganic forms. The present study was designed to find out the preventive role of Triticum aestivum against arsenic-induced oxidative stress in the liver of Swiss albino mice Methods: The protective role of T. aestivum (Wheatgrass) against arsenic-induced hepatic damages was investigated in adult Swiss albino mice. The animals were divided in to four groups: (i) Control group – only vehicle (double distilled water), (ii) T. aestivum treated group-20 ml/kg body weight (b.wt.), orally (iii) NaAsO2 treated group- 4.0 mg/kg b.wt., and orally (iv) combination group – T. aestivum leaves extract (20 ml/kg b.wt.) and NaAsO2 (4.0 mg/kg/b.wt.). Bodyweight and liver weight were measured in the process. Activities of marker enzymes such as alkaline phosphatase (ALP), Glutamic oxaloacetic transaminase, and glutamic pyruvic transaminase were measured in serum. Activities of lipid peroxidation (LPO), glutathione (GSH), and Lactate dehydrogenase (LDH) were measured in the liver. Results: The results indicated that arsenic intoxication caused a decrease in b.wt. and liver weight. Arsenic intoxication significantly increased hepatic LPO, Serum Glutamate Oxaloacetate Transaminase (SGOT), and Serum Glutamate Pyruvate Transaminase (SGPT) activities whereas significantly decreased hepatic GSH, hepatic LDH, and serum ALP activities. Combined treatment of T. aestivum and NaAsO2 showed: (i) An increase in body and liver weight, (ii) a significant decrease in LPO, SGOT, and SGPT activities, (iii) an elevation in GSH content, LDH, and serum ALP activities, as compared to NaAsO2 treated group. Conclusion: Thus, T. aestivum was found to be protective against arsenic-induced hepatic damages.